Wearable, Breathable and Waterproof Triboelectric Nanogenerators for Harvesting Human Motion and Raindrop Energy. Issue 6 (26th November 2021) - Yuan, Wei; Zhang, Chuguo; Zhang, Baofeng; Wei, Xuelian; Yang, Ou; Liu, Yuebo; He, Lixia; Cui, Shengnan; Wang, Jie; Wang, Zhong Lin
Abstract: Smart textiles capable of harvesting biomechanical energy via triboelectric effect have been well developed in the field of self‐powered wearable electronic products. However, it is still a challenge to manufacture self‐charging wearable electronic products with features of high triboelectric output, breathability and water resistance, simultaneously. Herein, a multifunctional wearable triboelectric nanogenerator (MW‐TENG) is designed with the functions of flexibility, excellent water resistance and air permeability to provide comfort and convenience in practical application. The maximum peak power density of the MW‐TENG can reach 1.03 W m –2 under the frequency of 3 Hz. Moreover, the MW‐TENG can be embedded in clothes and shoes to drive wearable electronic devices by harvesting human mechanical energy and raindrop energy. This work not only presents a kind of MW‐TENG with the functions of flexible, breathable, and waterproof, but also provides a practical strategy to design multifunctional self‐powered wearable electronic devices. Abstract : Based on the flexibility, excellent water resistance and air permeability of microporous polytetrafluoroethylene film and conductive fiber materials, it provides comfort and convenience for multifunctional wearable triboelectric nanogenerator (MW‐TENG) in practical applications. The maximum peak power density of the MW‐TENG can reach 1.03 W m –2, which can be embedded in clothes and shoes to harvest human mechanical energy and raindrop energy.